МАРКЕТИНГОВІ АСПЕКТИ ОРГАНІЗАЦІЇ БЛІЦКОНКУРСУ НА НОВИЙ ЛОГОТИП ЧЕРНІВЕЦЬКОГО НАЦІОНАЛЬНОГО УНІВЕРСИТЕТУ ІМЕНІ ЮРІЯ ФЕДЬКОВИЧА У ПАНДЕМІЙНИЙ ПЕРІОД - Вардеванян, Вардан Альбертович; Vardevanyan, Vardan; Vardevanian, Vardan (Черкаський державний технологічний університет, 2021)
У статті описано маркетингові аспекти організації бліцконкурсу на новий логотип Чернівецького національного університету імені Юрія Федьковича у пандемійний період. У статті описано типові бар’єри, з якими стикаються організатори конкурсів для навчальних закладів. Подано детальний опис методики проведення успішного конкурсу на новий логотип. Основними пунктами в організації бліцконкурсу автор визначає такі, як: чітке визначення цільової аудиторії бліцконкурсу, тривалість конкурсу, мотив участі в конкурсі потенційних учасників, проведення експертної оцінки конкурсних проєктів, текст положення про конкурс. Поетапно описуються кроки з організації бліцконкурсу. На першому етапі відбувається збір конкурсних робіт. Важливими складовими тут виступають умови конкурсу, які автор детально описує. На другому етапі відбувається експертна оцінка та затвердження нового логотипу. Успішне завершення конкурсу також залежить від добре підготовлених умов для проведення експертних оцінок та інших завершальних актів. The author of the article describes the marketing aspects of the organization of competition of blitz on the new logotype of the Yuriy Fedkovych Chernivtsi National University in a pandemic period. Typical barriers into that the organizers of competitions run for educational establishments are described in the article. Organizational barriers, financial barriers, expert and post-competitive barriers, come forward as such barriers. An author offers the detailed description of the methodology of realization of successful competition on a new logotype. By basic points in the organization of the blitz competition the author determines such as: clear determination of the target audience of the blitz competition, duration of competition, reason of participating in a competition, realization of expert estimation of competitive projects, text of position about a competition. Steps are stage-by-stage described from the organization of the blitz contest. There is a collection of competitive works on the first stage. As important constituents the terms of competition come forward here. In the organization of the blitz competition there were lifted restrictions to the participants, text and maintenance of terms of participation are brief in a competition, in times reduced the terms of holding competition (to one week), put right effective communication with the blitz contest participants. There are an expert estimation and claim of a new logotype on the second stage. Successful completion of competition also depends on well-prepared terms for realization of expert estimates and other finishing acts. The basic moments of first-minings are forming of competencies, that experts and selection of experts that answer the marked competencies must own. It is in addition, needed to prepare to the estimation sent competitive projects logotypes and comfortable format of expert estimation of competitive works. The clear criteria of project evaluations logotypes and questionnaire of expert estimates belong to such terms.
MARKETING ASPECTS OF ORGANIZATION OF BLITZ COMPETITION ON THE NEW LOGOTYPE OF YURIY FEDKOVYCH CHERNIVTSI NATIONAL UNIVERSITY IN A PANDEMIC PERIOD
Keywords: маркетинг; логотип; конкурс логотипів; бліцконкурс логотипів; логотип навчального закладу; логотип Чернівецького національного університету імені Юрія Федьковича; marketing; logotype; competition of logotypes; blitz competition logotypes; logotype of educational establishment; logotype of the Yuriy Fedkovych Chernivtsi national university